Social and Economic Importance of Managing Secondary Resources in Closed Cycle Economy - V. Yu. Garnova (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article reveals key aspects of managing secondary resources in closed cycle economy, whose ideology implies zero-waste manufacturing and careful attitude to the environment in accordance with the concept of sustainable development being implemented in conditions of permanent institutional restructuring. Today when the model of manufacturing arrangement is linear, the impact on nature is not taken into account adequately: ecologically unstable resources are used, waste is utilized and damage is not evaluated in a proper way. Joining the closed cycle economy presupposes thorough selection of raw materials, whose waste can be recycled and repeatedly used in production process (as a renewable energy). In altered conditions of implementing business-processes a new approach to managing secondary resources will be needed. Special attention will be paid to information-analytical and engineering – technological support. Economic expediency of using secondary resources was shown on practical examples, it is necessary to extend financial opportunities for business entities through well-balanced managerial solutions. The experience of best practices demonstrates that advanced innovation developments rely on max proved consumption of resources, which envisages repeated use of waste that could raise profitability of business and prevent unfavorable ecological impact on the environment.